Investigation of drug use at primary health centres in Nashik, Maharashtra, India - Shivgunde, Prashant P.; Kodilkar, Archana D. (International Journal of Research in Medical Sciences, 2019)
Background: By recognizing the need to promote rational utilization of medicines, the World Health Organization (WHO) in collaboration with the International Network for Rational Use of Drugs (INRUD) developed a set of core indicators. This study aimed to investigate drug use based on it. Methods: The study was performed in Primary Health Centers (PHC) in Nashik District, Maharashtra, India. Prescriptions data for the last one year from PHCs were sampled out retrospectively. Outpatients from PHCs were selected, observed and interviewed for the patient-care indicators, prospectively. Pharmacy personnel was interviewed for the facility-specific indicators. The data were analyzed; results and conclusions were drawn. Results: The average number of drugs per prescription was 3.48 (SD=0.36). The percentages of drugs prescribed by generic name and from Essential Drug List or formulary were 83.98% and 68.97% respectively. The percentages of encounters with antibiotics and injections were 60.33% and 50.83% respectively. The average consultation and dispensing times were 3.89 minutes and 58.28 seconds respectively. 98.19% of the prescribed drugs were actually dispensed. 67.27% of the dispensed drugs were labelled. The percentage of patients’ knowledge of the correct dosage was 87.78%. The percentage availability of the EDL or formulary was 100% and of the key drugs in the stock was 85.71%. Conclusions: The need for improvement in prescribing practices can be encouraged by devising strategies such as training to physicians, rewards systems, etc. There should be plans to increase staff members for a particular working period and to educate patients with healthcare, hygiene, medicines’ compliance and common diseases.